2017
DOI: 10.21608/taec.2017.11934
|View full text |Cite
|
Sign up to set email alerts
|

Bryophytes of Libya. II. Musci: an annotated checklist

Abstract: A list is given for the, hitherto, known moss flora of Libya. It includes 102 taxa, belonging to 45 genera in 16 families and 8 orders under class Bryopsida, and their distribution in 20 surveyed localities. Significant annotations are given regarding distribution of the taxa in Libya, in the Mediterranean area, dominance and rarity, old and new records, other relevant information and a list of synonyms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…the remaining mosses had been recorded recently by and Youssef et al (2018). It is worth mentioning that all the taxa reported in this work are recorded here for the first time from Gharyan area except Bryum dichotomum (el-Saadawi et al, 2017). the only earlier work on Gharyan was that of Bottini (1914).…”
Section: Results and Commentsmentioning
confidence: 52%
See 1 more Smart Citation
“…the remaining mosses had been recorded recently by and Youssef et al (2018). It is worth mentioning that all the taxa reported in this work are recorded here for the first time from Gharyan area except Bryum dichotomum (el-Saadawi et al, 2017). the only earlier work on Gharyan was that of Bottini (1914).…”
Section: Results and Commentsmentioning
confidence: 52%
“…the list of mosses of the Mediterranean area published by ros et al (2013) showed that a total of 91 taxa were known from Libya. records continued and the number of mosses known from Libya reached 102 taxa in the latest list published by el-Saadawi et al (2017). the 102 taxa belong to 45 genera, in 16 families and 8 orders all under class Bryopsida.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is based on the floristic information pertaining to the 13 hepatics of Egypt given by El-Saadawi and Shabbara (2007) and other references therein included particularly Arnell (1963), Jovet-Ast and Bischler (1970), Bischler (1993) and Ros et al (2007), which included details of collection data and distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Just over 200 bryophytes are, hitherto, known from Egypt (El-Saadawi and Shabbara, 2007;El-Saadawi et al, 2015;El-Sakaty et al, 2018;Khalil and Farag, 2018;Hassan et al, 2019;Taha and Holyoak in Ellis et al, 2019;Taha, 2020). The majority (188 taxa) are mosses while only 13 species belong to the liverworts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation